Synthesis of Glucopyranosyl Acetic from Sago Flour as Raw Material for the Synthetic Polymers - Dali, Arniah; Dali, Nasriadi; Dali, Seniwati; Amalia, Hilda Ayu Melvi (Indonesian Journal of Chemical Research, 2021)
Synthesis of glucopyranosyl acetic from sago flour as raw material for the synthetic polymers has been successfully carried out. The synthesis product is obtained through two reaction stages, namely the hydrolysis and esterification reactions. Sago flour is hydrolyzed with 25% HCl and neutralized with 45% NaOH. Glucose hydrolysis of sago starch and acetic anhydride was esterified using a zinc chloride catalyst. Synthesis product was obtained as a white solid substance (57.31% recovery), a melting point of 110 - 111oC, and Rf 0.79 on TLC (SiO2, n-hexane: ethyl acetate = 9:1 v/v). The results of the analysis of synthesis products with FTIR and GC-MS spectrometers showed that the synthesis product was glucopyranosyl acetic or 2,3,4,6-tetra-O-acetyl glucopyranose.